THE ROLE OF CAREER SELF-EFFICACY IN DEVELOPING CAREER MATURITY AMONG STUDENTS WITH DISABILITIES - Nurul Hidayah Multazam; Andi Nasrawati Hamid; Rahmawati Syam (CV. Lafadz Jaya, 2026)
Career development among university students with disabilities remains a significant concern due to structural barriers, limited access to inclusive career services, and restricted employment opportunities. This study aims to examine the role of career self-efficacy in developing career maturity among university students with disabilities. A quantitative explanatory design was employed involving 76 students with disabilities in Makassar selected through total sampling. Data were collected using the Career Decision-Making Self-Efficacy Scale–Short Form and the Career Maturity Inventory–Form C, and analyzed using simple linear regression. The findings reveal that career self-efficacy has a positive and significant effect on career maturity. Students with higher confidence in self-appraisal, occupational information seeking, goal selection, planning, and problem solving demonstrate greater career readiness, with self-appraisal contributing most strongly. Strengthening career self-efficacy and enhancing inclusive institutional support are essential to optimize career development outcomes for students with disabilities.